2010
DOI: 10.2105/ajph.2009.187179
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Fatalities From Distracted Driving in the United States, 1999 to 2008

Abstract: Distracted driving is a growing public safety hazard. Specifically, the dramatic rise in texting volume since 2005 appeared to be contributing to an alarming rise in distracted driving fatalities. Legislation enacting texting bans should be paired with effective enforcement to deter drivers from using cell phones while driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(158 citation statements)
references
References 20 publications
3
152
1
2
Order By: Relevance
“…2 As inexperienced drivers, teenagers commonly make errors that contribute to their high crash rate, including driving too fast for conditions, inadequate visual scanning of the road (driver is paying attention to driving but fails to see a hazard), and driving while distracted. [3][4][5] Distracted driving occurs when a driver diverts attention away from the driving task and instead to "an object, person, task, or event not related to driving." 6 As teenage cell phone ownership and texting have become ubiquitous in the United States, 7,8 distracted driving because of texting while driving (TWD) has emerged as an important teenage driver safety issue.…”
Section: Resultsmentioning
confidence: 99%
“…2 As inexperienced drivers, teenagers commonly make errors that contribute to their high crash rate, including driving too fast for conditions, inadequate visual scanning of the road (driver is paying attention to driving but fails to see a hazard), and driving while distracted. [3][4][5] Distracted driving occurs when a driver diverts attention away from the driving task and instead to "an object, person, task, or event not related to driving." 6 As teenage cell phone ownership and texting have become ubiquitous in the United States, 7,8 distracted driving because of texting while driving (TWD) has emerged as an important teenage driver safety issue.…”
Section: Resultsmentioning
confidence: 99%
“…This synthesis of driving performance research is convergent with the naturalistic, self-report and epidemiological research on texting and driving (Olson, Hanowski, Hickman & Sudweeks, 2009;Tison, Chaudhary & Cosgrove, 2011;Wilson & Stimpson, 2010). The accumulated evidence across research approaches for the safety costs of text messaging while driving is uniformly negative, unequivocal and convergent.…”
Section: Discussionmentioning
confidence: 52%
“…Wilson and Stimpson (2010) conducted a multivariate regression analysis of the FARS database (Fatality Accident Reporting System, U.S.) and found that the percent of total fatalities from distracted driving increased from 10.9 percent in 1999 to 15.8 percent in 2008. The increase in fatalities from 2002 to 2007 is likely the result of year over year increases in text messaging while driving: the study concluded that an estimated 16,141 additional fatalities resulted from texting while driving for that time period.…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive source for fatal crash data for the United States is the FARS maintained by the National Highway Traffic Safety Administration. FARS data come from a variety of sources including police reports, state registration files, state licensing files, vital statistics, death certificates, hospital records, and emergency medical or autopsy records (Wilson & Stimpson 2010). To be reported as a fatal crash in the FARS system, a crash-related death or deaths must occur within 30 days of the crash.…”
Section: Data Sources and Methodologymentioning
confidence: 99%